Advances in research on fine motion control of prosthesis fingers with brain-computer interface - Di GAN; Hui HUANG; Chengzhi LI; Shiyu ZHANG; Shiyuan WANG; Tao WANG (Zhongguo Linchuang Yixue)
The deficiency of fingers due to various reasons leads to a certain degree of loss of full or part hand functions. Physical and mental health of patients are seriously affected, and patients have varying degrees of reduced quality of life. Prosthesis fingers play an important role in completing the body shape and enhancing patients’ self-confidence and self-esteem. However, how to make prosthesis fingers perform coordinated movements and restore complete functions is a crucial problem that urgently needs to be solved. This paper reviews the methods of brain-computer interface controlled fine finger movements and elaborates on the origin, current situation, and advancements of the development of this technology, laying a foundation for subsequent research, with the expectation of helping patients solve the problems arising from the insufficiency or absence of finger functions.